2014
DOI: 10.1080/09712119.2014.887009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ascorbic acid administration on erythrocyte osmotic fragility in rabbits (Oryctolagus cuniculus) subjected to road transportation

Abstract: The physiological responses of erythrocytes of rabbits transported by road for 2 h under hot-humid climate and the ameliorating effect of ascorbic acid (AA) were investigated. Nine rabbits served as experimental (treated) and were administered AA orally at a dose of 100 mg/kg body weight, while seven other rabbits served as control and were given equivalent of sterile water only. Thirty minutes after AA administration, the rabbits were transported. The erythrocyte osmotic fragility (EOF) values recorded in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The result of (EOF) showed that CD increased haemolysis in rabbits, and the effect was more evident in CD-fed group only than CD groups, treated with resveratrol. The result agrees with the finding of [11], which showed that exposure of rabbits to oxidative stress increased haemolysis. Continuous exposure to ROS renders the erythrocyte to be sensitive to redox imbalance that alters its mechanical properties and resulting into oxidative stress [28,29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The result of (EOF) showed that CD increased haemolysis in rabbits, and the effect was more evident in CD-fed group only than CD groups, treated with resveratrol. The result agrees with the finding of [11], which showed that exposure of rabbits to oxidative stress increased haemolysis. Continuous exposure to ROS renders the erythrocyte to be sensitive to redox imbalance that alters its mechanical properties and resulting into oxidative stress [28,29].…”
Section: Discussionsupporting
confidence: 92%
“…The erythrocyte membrane is inertly connected with membrane stability and functions due to relative composition of fatty acids, phospholipids and cholesterol [10]. Recently, [11] reported that exposure of rabbits to oxidative stress increased haemolysis, which was ameliorated by ascorbic acid. Thus measures aimed at preventing or reducing ROS formation in the cells especially involving the administration of antioxidants may be an efficient means of reducing the damage induced in cell membrane [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The EOF is an important biomarker of oxidative stress, which may be utilised as a biomarker for heat stress in laying hens (Sinkalu et al, 2014). It may be used in broiler chickens to diagnose oxidative stress, having been demonstrated to serve as a biomarker of transport-induced oxidative stress, under high ambient temperature conditions, and as a reliable method for diagnosis of oxidative stress in quails (Minka and Ayo, 2013) and rabbits (Ayo et al, 2014). Furthermore, high levels of cortisosterone and heat-shock protein 70 may indicate levels of heat stressed (Zulkifli et al, 2009), and could result in high intensity levels of fear responses, evidenced by long tonic immobility in heat-stress broiler chickens (Al-Aquil et al, 2009).…”
Section: Biomarkers Of Heat Stress In Broiler Chickensmentioning
confidence: 99%
“…The cytosolic antioxidant system includes enzymatic (superoxide dismutase, catalase, and glutathione peroxidase) and non-enzymatic antioxidants (ascorbic acid, vitamin E, and glutathione), while the membrane mainly comprises of vitamin E as the major, lipid-soluble chain-breaking antioxidant [24]. Studies on the effect of antioxidants such as Vitamin C, Vitamin E, L-carnitine, β-carotene, α-lipoic acid and melatonin, on osmotic fragility have focused on supplementation [25][26][27][28][29][30][31][32][33][34][35][36]. Studies on storage and osmotic fragility have shown that osmotic fragility increases with prolonged storage [8,[37][38][39][40] and varies with different additive solutions [41,42].…”
Section: Introductionmentioning
confidence: 99%